Copper Content of Surface Waters in Mures County, Romania. (2015) - Morar, Florica
Abstract: The paper presents a comparative study regarding the presence of copper in drinkable waters in various localities in Mures County. In certain places (Târnăveni, Tîrgu Mureş) there are persistent pollution sources that can affect the quality of water, this is why the study is welcome for the interpretation of the evolution of the presence of heavy metals (in this case, copper). Through this paper we wish to emphasize the necessity for regular monitoring of drinkable water in areas that are more or less polluted. Samples were taken from wells and taps in more localities in Mureş county in the past two years: 2013 and 2014. The method used was inductively coupled plasma atomic spectroscopy (ICPOES). Sampling was made in accordance with ISO5667-1 and the method is ISO 11885: 2009 SREN. The six analyzed samples did not present evidence of excess of CMA (0, 1 mg / l). The highest copper content value was recorded in sample 2 (15.391 mg / l, in 2013, 15 851 mg / l in 2014 respectively).